2014
DOI: 10.1007/s10840-014-9904-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cardioversion on asymptomatic cerebral lesions following atrial fibrillation ablation

Abstract: Cardioversion during AF ablation significantly increased the risk of asymptomatic cerebral lesions on MRI following the procedure. Additional studies are required to further verify the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A number of studies have shown that intraprocedural electrical cardioversion is an independent predictor of SCLs. 25 , 29 , 42 Mechanistically, this might relate to the dislodgement of thrombotic material from equipment—or from fresh ablation lesions—due to the sudden movement caused by direct current cardioversion or by restoration of atrial contraction.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that intraprocedural electrical cardioversion is an independent predictor of SCLs. 25 , 29 , 42 Mechanistically, this might relate to the dislodgement of thrombotic material from equipment—or from fresh ablation lesions—due to the sudden movement caused by direct current cardioversion or by restoration of atrial contraction.…”
Section: Introductionmentioning
confidence: 99%